MAKAN BERGIZI DAN HIDUP PENUH PRESTASI - Sitoayu, Laras; Putri, Vira Herliana; Lutfiani, Wenny; Rumana, Nanda Aula (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
Abstract Teenagers, especially school children, are very vulnerable to the problems of nutrition, both over nutrition, lack of nutrition and indequate nutrition. Moreover, at the age of adolescence is very easily influenced by the environment. The influence of the environment that is not good, which is related to diet and eating habits will have a negative impact in the future. Teenagers tend to go along with choosing unhealthy foods, and as a result can reduce performance in school and threaten health in the future such as degenerative diseases. For this reason, it is important to hold a nutrition education about eating with balance nutrition to live a full life of achievement. This activity is one of collaboration community service activities between the Nutrition Study Program of the Faculty of Health Sciences (FIKes) with the Faculty of Teacher Training and Education. Aims of this activity is to increase the knowledge of students of SMPN 220 West Jakarta regarding eating with balance nutrition to get an achievement life, it is hoped that students of SMPN 220 West Jakarta can practice balanced nutrition eating in daily life. As many as 35 students attended and participated in this activity well. Activities like this are important to be carried out every year with different targets, so that the socialization of nutrition food to support increased achievement can be achieved properly. Keyword: Nutritious food, adolescent dietary patterns, nutrition for achievement AbstrakRemaja terutama anak sekolah sangat rentan dihinggapi masalah gizi, baik gizi lebih, gizi kurang maupun kecukupan asupan gizi. Terlebih lagi diusia remaja sangat mudah dipengaruhi oleh lingkungan sekitar. Pengaruh lingkungan sekitar yang tidak baik, yang berkaitan dengan pola makan dan kebiasaan makan akan berdampak negatif dimasa yang akan datang.Remaja cenderung ikut-ikutan memilih makanan yang tidak sehat, dan akibatnya dapat menurunkan prestasi di sekolah dan mengancam kesehatan dimasa yang akan datang seperti penyakit degeneratif. Untuk itu, penting diadakan edukasi gizi mengenai makan bergizi untuk hidup penuh pretasi pada remaja. Kegiatan ini merupakan salah satu rangkaian kegiatan kolaborasi pengabdian masyarakat antaraProgram Studi Gizi Fakultas Ilmu-ilmu Kesehatan (FIKes)dengan Fakultas Keguruan dan Ilmu Pendidikan. Tujuan kegiatan ini adalah meningkatkan pengetahuan siswa/i SMPN 220 Jakarta Barat mengenai Makan bergizi untuk memperoleh hidup yang berprestasi, diharapkan siswa/i SMPN 220 Jakarta Barat dapat mempraktikkan makan bergizi seimbang dalam kehidupan sehari-hari. Sebanyak 35siswa/i SMPN 220 Jakarta Barat hadir dan mengikuti kegiatan ini dengan baik. Kegiatan seperti ini penting dilakukan setiap tahun dengan target sasaran yang berbeda-beda, sehingga sosialisasi makan bergizi untuk menunjang peningkatan prestasi dapat tercapai dengan baik. Kata kunci :Makan bergizi, pola makan remaja, gizi untuk prestasi